Polymeric frameworks as organic semiconductors with controlled electronic properties - Sakaushi, Ken; Nickerl, Georg; Kandpal, Hem Chandra; Cano-Cortes, Laura; Gemming, Thomas; Eckert, Juergen; Kaskel, Stefan; Van Den Brink, Jeroen (Journal of Physical Chemistry Letters, 2013)
The rational assembly of monomers, in principle, enables the design of a specific periodicity of polymeric frameworks, leading to a tailored set of electronic structure properties in these solid-state materials. The further development of these emerging systems requires a combination of both experimental and theoretical studies. Here, we investigated the electronic structures of two-dimensional polymeric frameworks based on triazine and benzene rings by means of electrochemical techniques. The experimental density of states was obtained from quasi-open-circuit voltage measurements through a galvanostatic intermittent titration technique, which we show to be in excellent agreement with first-principles calculations performed for two- and three-dimensional structures of these polymeric frameworks. These findings suggest that the electronic properties depend not only on the number of stacked layers but also on the ratio of the different aromatic rings. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electrochemistry; electronic property; organic semiconductors; polymeric frameworks; rational assembly